Analisis Struktur Modal dan Profitabilitas terhadap Harga Saham PT Wijaya Karya Tbk: Literatur Riview - Aprilia Hanifah Nur Cahyati; Ajeng Tita Nawangsari (AKUNTANSI 45, 2026)
This study was conducted with the aim of analyzing the relationship between capital structure and profitability levels on the stock price movement of PT Wijaya Karya Tbk, using a literature review approach. The analysis of capital structure in this study focuses on the Debt to Equity Ratio (DER), while profitability is assessed using Return on Assets (ROA) and Return on Equity (ROE) as the primary indicators. The method employed is descriptive qualitative through a literature study, which examines previous research concerning the relationship between capital structure, profitability, and stock price fluctuations. The findings suggest that most prior studies indicate that the Debt to Equity Ratio (DER) has a negative effect on stock prices, whereas Return on Assets (ROA) and Return on Equity (ROE) generally have a positive impact. The study also reveals that an optimal capital structure combined with high profitability can enhance investor confidence and contribute to stock price appreciation. This review offers a conceptual understanding of the importance of capital structure management and profitability optimization in supporting corporate stock performance.